A quick and low-intensity method for oral administration to large numbers of mice: A possible alternative to oral gavage. (April 2022) - Neto, Tiago; Faustino-Rocha, Ana I; Gil da Costa, Rui M; Medeiros, Rui; Oliveira, Paula A
Oral administration of medication to experimental animals is a cause of significant stress. When coupled to animals who are already under strenuous circumstances due to the disease being modelled, there is a significant risk for increased morbidity and mortality, thus influencing the results. Faced with these constraints, a low-intensity method for oral administration was developed, based solely on the natural behaviour of the animals and minimal conditioning, in which precise doses of medication were administered in a locally available, standard wheat cookie fragment, providing both a palatable vehicle and an absorbent matrix for the medication. Fast administration to large numbers of animals was thus achieved, safeguarding the animals' welfare and ensuring ease of handling. This method is a promising alternative to oral gavage in pre-clinical drug studies with laboratory mice.